Quercetin Augments Cisplatin-Induced Apoptosis, DNA Damage Response, and MiR-22 Expression While It Prevents DNA Repair in Osteosarcoma Cells - Malakoti, Faezeh; Majidinia, Maryam; Ahmadi, Yasin; Yousefi, Bahman; Shanebandi, Darioush (Drug Research, 2022)
Background Osteosarcoma (OS) patients are commonly treated with chemotherapeutic agents like cisplatin (Cis). Quercetin with fewer side effects can improve the potency of chemotherapy and be used in combinational therapies. Herein, we aimed to evaluate the effects of Cis plus quercetin on DNA damage response (DDR), DNA repair, and apoptosis in Saos-2 cells.Methods The effects of Cis and quercetin single or in combination on Saos-2 cell viability and the cytotoxicity of the drugs were measured by MTT assay. The expression of DDR and repair components including P53, ATM, ATR, RAD51, and H2AX, and also miR-22 were analyzed by real-time PCR. The rate of apoptosis was measured by flow cytometry.Results Quercetin potentiated the cytotoxic effects of Cis in Saos-2 cells. The IC50 of Cis reduced from 6.12 µM to 4.25 µM. The combination of quercetin and Cis was associated with the up-regulation of miR-22 and DDR components, including P53, ATM, ATR, and H2AX as well as the down-regulation of RAD51. Moreover, this combined regimen significantly induced apoptosis in Saos-2 cells compared to mono drugs.Conclusion The co-treatment of quercetin and Cis can accelerate DNA damage, DNA damage response, and apoptosis while interfering with the DNA repair process in Saos-2 cells. Moreover, this combination provokes the tumor suppressor miR-22 expression in these cells.
Keywords: Polyphenols; Flavonoids; DNA damage; Bone tumor; Chemotherapy; miRNA